Blood brother : Jonathan Daniels and his sacrifice for civil rights - Wallace, Rich (Calkins Creek, an imprint of Highlights, 2016)
"Rich Wallace and Sandra Neil Wallace explore what led [Jonathan Myrick] Daniels to the moment of his death, the trial of his murderer, and how these events helped reshape both the legal and political climate of Lowndes County and the nation"--Amazon.